Control of p- and n-type Conduction in Thermoelectric Non-doped Mg2Si Thin Films Prepared by Sputtering Method. (5th February 2018) - Kurokawa, Mao; Shimizu, Takao; Uehara, Mutsuo; Katagiri, Atsuo; Akiyama, Kensuke; Matsushima, Masaaki; Uchida, Hiroshi; Kimura, Yoshisato; Funakubo, Hiroshi
ABSTRACT: A method for controlling the conduction-type in Mg2 Si films without doping is investigated. Mg2 Si films exhibit p-type conduction after a post-heat treatment up to 500 °C in atmospheric He. However, covering the films with Mg ribbon during a subsequent heat treatment at 500 °C converts the conduction to n-type, demonstrating that the heat treatment atmosphere can control the conduction type. Based on the reported first principles calculations suggesting that interstitial Mg and Mg vacancies in Mg2 Si are the origins of n-type and p-type conduction, respectively, the post-heat treatment in He induces Mg vacancies due to the evaporation of Mg from the film, resulting in p-type conduction. The subsequent heat treatment when the film is covered with Mg ribbon fills the Mg vacancies and the additional interstitial Mg is incorporated, resulting in n-type conduction. These observations differ from the reported data for heat treatment of stable n-type conduction in non-doped Mg2 Si-sintered bodies and may realize a novel control method for the conduction type in Mg2 Si films.